O Museu Paulista de Mário Neme (1960-1973) - Silva, Tathianni Cristini da (2020)
This article analyzes the work of Mário Neme as Director of Paulista Museum, from 1960 to 1973. He became the Director after working with the organizing staff of the Historical Exhibition of the 40th Centenary of the City of São Paulo, in 1954. When Neme took office, the museum had serious financial and staff problems, with unfinished works since 1953. This prevented people from visiting the place. Despite the issues he faced, some actions and projects were implemented, bringing important changes to the museum: it was finally opened for visitation, the archeology section was improved, the museology course was implemented, and the museum became managed by the University of São Paulo; this turned the museum into a University Museum. Yearly reports and those prepared by the teams of researchers and staff of the institution were analyzed in the preparation of this paper. Interviews with museum staff and intellectuals were also carried out. Reading the documents and analyzing the interviews allowed realizing that, during Neme’s management, Paulista Museum was a research center under development and an important social space for intellectuals during that period.